Prospective mode of action of Ivermectin: SARS-CoV-2 - Vaishali M. Patil; Saroj Verma; Neeraj Masand (Elsevier, 2022)
The well-known anti-helminthic drug ivermectin (IVM) has been established as an example of drug repurposing for the management of SARS-CoV-2 infection. Various study has been done to understand the inhibitory mechanism of IVM against SARS-CoV-2 targets. Broadly, IVM has been categorized as a host-directed agent and the proposed mechanism involves inhibition of the IMPα/ß1-mediated nuclear import of viral proteins. In addition, in vitro/in vivo and molecular docking/dynamic simulation studies suggested multitargets mechanism of IVM against SARS-CoV-2. Present manuscript attempts to provide an overview of the detailed mechanism of action based on experimental and computational studies. The knowledge of binding interaction of IVM and SARS-CoV-2 targets will give the direction to developed new and potential anti-COVID agents.